Tracing the Threads: Unearthing the Historical Landscape of Islamic Guidance and Counseling in Indonesia - Muskinul Fuad; Abdul Kholiq; Mustain Mustain (Universitas Islam Negeri Sumatera Utara, 2026)
This study aims to trace and analyze the historical and epistemological development of Islamic Guidance and Counseling (IGC) studies in Indonesia, uncovering the interdisciplinary dynamics that have shaped its growth across guidance, counseling, and psychotherapy domains. This study uses a discourse-historical approach to demonstrate the dynamic and heterogeneous growth of Islamic Guidance and Counseling studies in Indonesia. This condition is observed accross the spectrum of research and development, which includes guidance, counseling, and psychotherapy. This discipline develops in an interdisciplinary manner with the influence of other knowledge such as Da'wah, Education, Islamic Psychology, and Sufism. While public university academics often restrict guidance and counseling to developmental education, those at State Islamic Universities prefer a broader, more clinical approach to Islamic guidance and counseling. Indonesian Islamic guidance and counseling is shaped by three epistemological schools: bayani (thematic interpretation), burhani (speculative philosophical-rational), and irfani (Sufistic spiritual interpretation of human issues). These three approaches are followed to understand guidance and counseling efforts toward humans. Starting from these three approaches, Islamic guidance and counseling researchers in Indonesia have succeeded in formulating various methods that can be used to produce Islamic Guidance and Counseling studies that are expected to answer challenges to Muslims in Indonesia.